Water supply conditions determine typical plantation water use strategies in Northern China - Yujia Chen; Tonggang Zha; Hongli Zhang; Lili Zhao; Ao Wang; Qingzhou Cui; Junling Song; Hengshuo Zhang; Yang Yu; Dongmei Wang (Journal of Hydrology: Regional Studies)
Study region: Beijing, northern China Study focus: In the context of climate change and increased extreme drought events, understanding the water use characteristics of typical tree species in semi-arid areas is crucial for evaluating plant adaptability and guiding sustainable forest management. However, there is limited literature on the response of water use strategies of different habitat plantations to changes in water supply conditions in northern China. The study assesses the δ2H and δ18O isotopic compositions of xylem and soil water within 100 cm of the soil surface in tree plantations, along with the δ13C values of plant leaves, over two consecutive hydrological years. The goal was to investigate the water use characteristics of Pinus tabuliformis and Acer truncatum in the mountainous and plain areas of Beijing, China. New hydrological insights for the region: According to the findings, during the growing seasons of 2021 (the drier years) and 2022 (the wetter years), the plantations in the mountainous areas primarily relied on shallow soil (0–20 cm, with an average water absorption rate of 35.75 %). While the water absorption ratio in the deep soil (60–100 cm) was significantly higher during the drier year compared to the wetter year (an increase of 23.87 %) in the plain area. The plantations in the mountainous area exhibited significantly higher leaf-level water use efficiency (WUEi) during the drier year (p < 0.05), while no significant difference was observed between 2021 and 2022 in the plain area. Therefore, when water is restricted, the plantations in mountainous area mainly enhance vegetation water use efficiency, while the plantations in plain area primarily adjust by converting water sources. Consequently, multiple factors affecting water supply conditions should be considered in an integrated manner, including precipitation and habitat. These insights provide valuable references for the sustainable development of plantations and the study of plant water source mechanisms.